2020
DOI: 10.1111/cid.12954
|View full text |Cite
|
Sign up to set email alerts
|

“Three‐in‐one” patient‐specific surgical guides for simultaneous dental implants in fibula flap jaw reconstruction: A prospective case series

Abstract: Background Conventional freehand immediate placement of dental implants is technically challenging in the jaw reconstructive surgery. Computer‐aided surgery might be the best solution, however, there has not been any standard approach to ensure the accuracy and efficiency of simultaneous dental implants in fibula flap jaw reconstruction. Purpose We aim to evaluate the clinical outcome of simultaneous dental implant in fibula flap using the “three‐in‐one” patient‐specific surgical guide (3‐in‐1‐PSSG) in an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Before this patient received the second flap with miniplates, there was a local infection and, consequently, loss of the implant-bearing part of the fibula due to poor soft tissue management over the residual part of the reconstruction plate ( Figure 3B ). Certainly, backward-planning including positioning of dental implants is possible before surgery ( 40 ), but reconstruction plates often impede reliable soft tissue management for dental implants ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before this patient received the second flap with miniplates, there was a local infection and, consequently, loss of the implant-bearing part of the fibula due to poor soft tissue management over the residual part of the reconstruction plate ( Figure 3B ). Certainly, backward-planning including positioning of dental implants is possible before surgery ( 40 ), but reconstruction plates often impede reliable soft tissue management for dental implants ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…When surgeons felt competent in this surgical procedure, the significantly increased proportions of tumor staging and concomitant surgery suggested that the complexity of surgery after 23 cases was higher than the earlier cases. The concomitant surgery, simultaneous dental implant placement with the aid of a “three-in-one” patient-specific surgical guide ( 35 ), was also a technically challenging procedure. Accordingly, a fluctuation of proficiency was observed at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our published methodology, the actual location of implants inserted was represented as the 3D models built from the postoperative CT scan ( 16 ). Long axes of the actual and the planned dental implants were compared to demonstrate the angle deviation in implant insertion.…”
Section: Methodsmentioning
confidence: 99%